2005
DOI: 10.1177/0033688205053481
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Cultural Instruction on Foreign Language Learning

Abstract: Many elementary EFL teachers in Taiwan have concerns in integrating target culture teaching into their language classrooms for reasons such as teachers’ limited knowledge of the target culture, lack of time, lack of methods and materials. In order to persuade more language teachers to teach target language culture, guidelines about designing an applicable cultural instruction and evidence about its effects on language learning are needed. In the study, the combination of an anthropology process and task-orient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 17 publications
2
15
0
Order By: Relevance
“…The respondents also said that studying language helped their vocabulary, grammatical structures and other grammatical items. Such a finding accords with Tsou (2005) who found that Taiwanese students benefited from such cultural immersion in language learning. Their language proficiency was significantly improved.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The respondents also said that studying language helped their vocabulary, grammatical structures and other grammatical items. Such a finding accords with Tsou (2005) who found that Taiwanese students benefited from such cultural immersion in language learning. Their language proficiency was significantly improved.…”
Section: Discussionsupporting
confidence: 87%
“…Besides, learning culture also contributes to the learning of language and some studies show that there is benefit to language learning deriving from learning culture. In a recent Taiwanese study, Tsou (2005) examined the effect of cultural instruction on foreign language learning. The researcher implemented culture instruction within two elementary EFL classrooms for one semester to see the effects of culture instruction on foreign language learning.…”
Section: The Benefits Of Teaching Culture In Language Classroomsmentioning
confidence: 99%
“…Therefore, Table 6 above shows that 78.6% of the students agree and strongly agree, whereas 7.1% disagree, 2.9% strongly disagree, and 11.4% are neutral. Tsou (2005) Table 7 shows that 25.7% of the respondents strongly agree and 51.4% agree with the statement, but 8.6% disagree, 2.9% strongly disagree, and 11.4% are neutral with this idea. Results clearly show that cultural knowledge is a pivotal in attaining linguistic proficiency.…”
Section: Results Related To the Questions Of The Studymentioning
confidence: 96%
“…In the 21 st century, researchers interest in teaching the target culture together with the target language has only peaked (Bennett, 1997;Cakir, 2006;Ho, 2009;Schuetze, 2008;Fox & Diaz-Greenberg, 2006;Drewelow, 2013;Barnes-Karol & Broner, 2010;Izadpanah, 2011;Jiang, 2012;Karabinar & Guler, 2012;Chlopek, 2008 andSercu, Gracia, andPrieto, 2004). Tsou (2005), Yeşil, and Demiröz (2017) each put forth that teaching the target culture has a positive motivational impact on students' proficiency levels in English. Cheung (2001) shows us that it also motivates teachers as well.…”
Section: Culture Teaching In Eltmentioning
confidence: 99%